Analisis faktor kepuasan pasien di rumah sakit - Detty, Ade Utia; Rizki, Fakhri; Liasari, Deni Eka (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The quality of healthcare service provision can be improved by detecting current problems, and important areas to recognize these problems through customer satisfaction assessment. Five general dimensions of service quality are tangible evidence, reliability, responsiveness, assurance, and empathy. If consumers see that the application of quality dimensions in daily work will significantly affect their needs and expectations, then this situation can lead to positive consumer behavior. Purpose: To analyze patient satisfaction factors at Bintang Amin Hospital. Method : This type of quantitative research with a cross-sectional research design, the population is all patients at Bintang Amin Hospital, the sampling technique used is purposive sampling with a sample of 100 respondents. The instrument uses a questionnaire and the statistical test used is the chi-square test. Results: The frequency distribution of reliability (63%) was good, assurance (59%) was good, tangible evidence (61%) was good, empathy (61%) was good, responsiveness (60%) was good, and satisfaction (64%) is satisfied. The results of the chi-square test p-value 0.000 ≤ 0.05. Conclusion: There is a relationship between reliability, assurance, tangibles, empathy, and responsiveness and satisfaction. Keywords: Assurance; Empathy; Reliability; Responsiveness; Satisfaction; Tangibles. Pendahuluan: Kualitas penyediaan pelayanan kesehatan dapat ditingkatkan dengan mendeteksi masalahnya saat ini, dan area penting untuk mengenali masalah tersebut melalui penilaian kepuasan pelanggan. Lima dimensi umum kualitas pelayanan berupa bukti fisik (tangible), kehandalan (reliability), daya tanggap (responsiveness), jaminan (assurance), dan empati (empathy). Apabila konsumen melihat bahwa penerapan dimensi kualitas dalam pekerjaan sehari-hari akan sangat memengaruhi kebutuhan dan harapan mereka, maka situasi ini dapat menyebabkan perilaku konsumen yang positif. Tujuan: Untuk menganalisis faktor kepuasan pasien di rumah sakit. Metode: Jenis penelitian kuantitatif dengan rancangan penelitian cross sectional, populasi adalah seluruh pasien di RS. Bintang Amin, teknik sampling yang digunakan adalah purposive sampling dengan sampel 100 responden. Instrumen menggunakan kuesioner dan uji statistic yang digunakan uji chi square. Hasil: Distribusi frekuensi kehandalan (63%) baik, jaminan (59%) baik, bukti fisik (61%) baik, empati (61%) baik, daya tanggap (60%) baik, dan kepuasan (64%) puas. Hasil uji chi square p value 0.000 ≤ 0.05. Simpulan: Ada hubungan faktor keandalan, jaminan, bukti fisik, empati, dan daya tanggap terhadap kepuasan. Kata Kunci: Bukti Fisik; Daya Tanggap; Empati; Jaminan; Kehandalan; Kepuasan.